1978
DOI: 10.3109/17453677809050088
|View full text |Cite
|
Sign up to set email alerts
|

Postural Equilibrium in Adolescent Idiopathic Scoliosis

Abstract: Postural equilibrium has been quantified by stabilometry in 57 patients with adolescent idiopathic scoliosis aged 10-16 years. Treatment was required in 39 cases whereof 18 were placed under observation only. The control group comprised 32 healthy children of the same age. An experimental design was made to vary the degree of difficulty of upright standing in four different test situations. The postural sway was analysed in the sagittal and lateral direction as well as in the area of total sway. The scoliotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
88
2
6

Year Published

1986
1986
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(102 citation statements)
references
References 8 publications
6
88
2
6
Order By: Relevance
“…Several authors have found alterations of proprioception and equilibrium control in scoliotic patients [1,[3][4][5][6][7][8][9][10]28]. Yamada [29] suggested that any disruption in the postural reflex system might induce scoliosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have found alterations of proprioception and equilibrium control in scoliotic patients [1,[3][4][5][6][7][8][9][10]28]. Yamada [29] suggested that any disruption in the postural reflex system might induce scoliosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical studies have shown abnormalities in the balance control and proprioception in scoliotic patients as compared with age-and gender-matched healthy controls. Patients with IS have been found to have abnormal postural perception [1][2][3][4], impaired dynamic balance control [5], as well as angle joint reproduction asymmetries [6,7]. Vibratory sensitivity has also been found to be abnormal, increased [8,9] or decreased [10] in IS patients.…”
Section: Introductionmentioning
confidence: 99%
“…These sensory issues can be explained by static or dynamic adaptive strategies. The static upright posture results from an increase of both the oscillation range [23] and the centre of pressure displacement [8,22]. Spinal deformity has no effect on trunk motion but influences movement between body segments (spine and limbs) [22].…”
Section: Introductionmentioning
confidence: 99%
“…The interpretation of this trend was a natural process of maturation. We did not encounter the abnormal findings in postural control in children with scoliosis reported by other investigators [8,12,22,23].…”
Section: Discussionmentioning
confidence: 51%
“…T o understand the development of IS, the postural control system has been studied. This system is an important factor in the stabilization of the body posture [23,23]. Next to the equilibrium system the orientation system of the brain also exerts control over the stabilization of body posture [13].…”
Section: Introductionmentioning
confidence: 99%